Best practice in global negotiation strategies for leaders and managers in the 21st century - Saee, John (Journal of Business Economics and Management, 2008)
This research article examines various types of negotiations and negotiation styles and best practice in global negotiations, which may be adopted by leaders and entrepreneurs under different conditions and cultural milieus to reach an agreement while conducting business across the globe.First published online: 14 Oct 2010